An experimental study on the impact of holy Qur’an recitation in reducing anxiety among preoperative patients in Indonesia - Saputro, Tatag Dwi; Wahyuningtyas, Eka Sakti; Kamal, Sodiq (Universitas Muhammadiyah Magelang, 2025)
Preoperative care begins upon the patient’s arrival in the operating room and continues until their transfer to the operating table. This stage is often associated with heightened anxiety among patients. Despite the prevalence of this issue, limited research has been conducted to evaluate the effect of Holy Qur'an recitation in alleviating preoperative anxiety. This study aimed to determine the effect of listening to Qur'an recitation (Murattal) on anxiety levels in preoperative patients in the Surgical Ward. A quasi-experimental design was employed, incorporating a pre-test and post-test with a control group design. The sample consisted of 32 respondents selected through non-probability purposive sampling. The intervention involved a single 15-minute session of listening to the recitation of Surah Al-Mulk via MP3 headphones, followed by a post-test evaluation. Statistical analyses included the Shapiro-Wilk test, homogeneity test, paired sample t-test, and independent sample t-test, with a significance threshold set at p < 0.05. The findings demonstrated a significant reduction in anxiety levels among preoperative patients following the Murattal Qur'an therapy. This suggests that Murattal therapy is an effective method for reducing anxiety and may serve as an alternative or complementary approach to managing anxiety among preoperative patients. Keywords: Anxiety, health innovation, healthcare provider, holy Qur'an, preoperative stage